Authentication of Hadith - Ahmed M. Hashim (International Institute of Islamic Thought, 2010)
This book attempts to construct criteria whereby one can validate (reject or accept) Prophetic traditions (hadiths) that are considered questionable. Such an attempt reflects Israr Ahmad Khan’s opinion that many of the hadiths in the canonical Sunni collections, which traditional hadith scholars consider to be authentic, are in fact, not so. Thus, Muslim scholars need to revisit these hadiths and apply a different methodology to demonstrate that they are fabricated. To this end, the author gives different criteria to aid in this sifting ...